EMOTIONAL DESIGN: A REVIEW OF THEORETICAL FOUNDATIONS, METHODOLOGIES, AND APPLICATIONS - I Made Marthana Yusa; I Ketut Ardhana; I Nyoman Darma Putra; Ida Bagus Gde Pujaastawa (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: This article reviews the theoretical foundations, methodologies, and applications of emotional design, a concept that emphasizes the importance of creating an emotional connection between users and products. The article provides an overview of the three levels of emotional design - visceral, behavioral, and reflective - and their underlying principles. Research methods: Deep and comprehensive review of literature from multidiscipline field of studies related to emotional design conducted with retrospective reasoning. The article then provides an overview of various applications of emotional design in product design and visual communication design, including digital interfaces, automotive design, and healthcare. The article concludes by discussing the future directions of emotional design research and its potential impact on the design industry. Findings: Emotional design is a promising approach to product design and visual communication design that can enhance the user experience by creating an emotional connection between users and products. The three levels of emotional design and various research methodologies can be used to measure emotional responses to design. Implications: Emotional design has been applied in various industries, and its potential impact on the design industry is significant. Future research in emotional design can explore the interplay between the different levels of emotional design and its impact on user behavior and product success.